Productivity and finance: the intangible assets channel - a firm level analysis - Demmou, Lilas (OECD Economics Department Working Papers, 2020)
Using a cross-country firm level panel dataset from 1995 to 2015, this paper revisits the finance-productivity nexus by looking at the role of intangible assets. It argues that due to their specific characteristics, such as valuation uncertainty and lower pledgeability, financing the purchase of intangible assets is more difficult than that of tangible assets. As a result, financial frictions are expected to be more binding for productivity growth in sectors where intangibles have become a pivotal component in firms production function. The analysis relies on a panel fixed effects econometric approach, several indices to capture financial frictions at the firm level and a new measure of intangible intensity at the industry level. We provide evidence that financial frictions act as a drag on productivity growth and especially so with respect to firms operating in intangible intensive sectors. These findings, which are robust to alternative specifications, shed light on the role of financial factors in explaining the productivity slowdown in OECD countries and provide support for using intangible intensity as a new dimension to proxy the relative exposure of industries to financing frictions